2017
DOI: 10.4028/www.scientific.net/ssp.268.379
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Characterisation of Konjac Glucomannan Gel as a Medical Phantom

Abstract: Acoustic properties are the main criteria to evaluate the compatibility of tested materials as a medical phantom. We determined the acoustic properties of konjac glucomannan (KGM) gel to verify its compatibility as a medical phantom. The acoustic properties measurement employed ultrasonic insertion technique and utilized two identical transducers of 5 MHz center frequencies. One KGM gel block with 5.62 mm thickness was used as sample to determine its longitudinal speed, acoustic impedance and attenuation coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Tissue mimicking materials (TMMs) are materials that mimic the acoustic properties of human tissues [1][2]. Thus, the values of acoustic properties are important to determine the compatibility of a tested material as a TMM [2][3]. The acoustic properties of human tissues are highly dependent on temperature and frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue mimicking materials (TMMs) are materials that mimic the acoustic properties of human tissues [1][2]. Thus, the values of acoustic properties are important to determine the compatibility of a tested material as a TMM [2][3]. The acoustic properties of human tissues are highly dependent on temperature and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers studied the potential of new ingredients as TMMs like gellum gum hydrogel [13] and Konjac-Carrageenan hydrogel [14]. In 2017, Mat Daud, Rohani and Jaafar determined the longitudinal speed, acoustic impedance and attenuation coefficient of Konjac Glucomannan (KGM) gel [2]. The result indicated that the KGM gel was compatible to be a TMM since its acoustic properties were in the range of the acoustic properties of human soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, a computerized system was developed, based on the LeCroy Wave Series digital oscilloscope, for online measurement of the acoustic properties of TMMs [8]. This system is based on an ultrasonic insertion technique (UIT) that uses two identical transducers aligned with one another [9,10]. Therefore, a sample has to be carefully inserted between transmitter and receiver such that its surface is perpendicular to both transducers, in order to ensure the accuracy of measurement [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This system is based on an ultrasonic insertion technique (UIT) that uses two identical transducers aligned with one another [9,10]. Therefore, a sample has to be carefully inserted between transmitter and receiver such that its surface is perpendicular to both transducers, in order to ensure the accuracy of measurement [9][10][11]. Furthermore, the developed system requires ultrasound pulse transmission in distilled water as the calibration procedure and the water temperature measurement, to calculate the acoustic properties of samples [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation